PENGARUH BIOCHAR COATED UREA TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium cepa var. aggregatum L.) DI TANAH BERPASIR - Sudarwati, Nurlaili; Supriyadi, Slamet; Rahman, Fahmi Arief; Yuhardi, Erick (JTSL (Jurnal Tanah dan Sumberdaya Lahan), 2026)
This study was conducted to evaluate the effect of chemical fertilizer coated with biochar on the growth of shallots (Allium ascalonicum L.) in sandy soil. The research was carried out at the Greenhouse of the Agroecotechnology Department, Faculty of Agriculture, Trunojoyo University of Madura, located in Telang Village, Kamal District, Bangkalan Regency, Madura, at an altitude of approximately 5 meters above sea level, from August to December 2023. A non-factorial Completely Randomized Design (CRD) was used, consisting of six treatments: P0 (control), P1 (recommended fertilizer), P2 (80% urea coated with rice husk biochar + bentonite), P3 (100% urea coated with rice husk biochar + bentonite), P4 (80% urea coated with corn cob biochar + bentonite), and P5 (100% urea coated with corn cob biochar + bentonite). The results showed that the application of biochar-coated urea fertilizer had no significant effect on plant growth and yield parameters such as plant height, number of leaves, number of tillers, number of tubers, tuber diameter, and root volume. However, plant height at 42 days after transplanting (DAT), the number of tillers at 42–63 DAT, and chlorophyll content showed significant differences among the treatments. Additionally, soil analysis parameters—including pH, organic carbon (C-organic), and soil nitrogen (N)—showed significant responses to the treatments.